Research on the Application of Online-Offline Blended Teaching Model Based on OBE Concept Combined with Chaoxing Learning Platform in Practical Teaching of Clinical Nursing Students - Yanni Luo; Yali Gu; Yuke Chen; Xiuping Huang; Huatao Qin; Qiujiao Liao; Hongfang Yang; Zhiqiong Meng; Xiaoting He (Journal of Artificial Intelligence and Information, 2026)
Objective: To explore the application effect of the online-offline blended teaching model based on Outcome-Based Education (OBE) concept combined with Chaoxing Learning Platform in practical teaching of clinical nursing students. Methods: A non-concurrent controlled study design was adopted. A total of 43 nursing interns of 2024 cohort from the Affiliated Hospital of Youjiang Medical University for Nationalities were selected as the control group receiving traditional teaching methods, while 59 nursing interns of 2025 cohort were assigned to the experimental group adopting the OBE-based online-offline blended teaching model supported by Chaoxing Learning Platform. Scores of self-directed learning ability, critical thinking ability and core nursing competency of nursing students at the end of internship were compared between the two groups, and the teaching satisfaction of the experimental group was investigated. Results: The total score and subscale scores of learning motivation and self-management for self-directed learning ability in the experimental group were significantly higher than those in the control group (P